2009
DOI: 10.1200/jco.2008.19.5933
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Tumor Response at the End of Therapy in Group III Rhabdomyosarcoma: A Report From the Children's Oncology Group

Abstract: A B S T R A C T PurposeSome patients with rhabdomyosarcoma (RMS) achieve less than a complete response (CR) despite receiving all planned therapy. We assessed the impact of best response at the completion of all therapy on patient outcome. Patients and MethodsWe studied 419 clinical group III participants who completed all protocol therapy without developing progressive disease for Intergroup Rhabdomyosarcoma Study (IRS) IV. Response (complete resolution [CR], partial response [PR; Ն 50% decrease], or no respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 28 publications
(9 reference statements)
2
65
4
Order By: Relevance
“…Second look surgeries of residual tumor either during or at the end of therapy have previously been evaluated. Persistence of radiographic masses at the end of therapy is well known, but biologic potential is uncertain, and resection of residual masses at the end of therapy has not been associated with improved outcome [26]. However, second look surgeries may demonstrate whether viable tumor is present, which has decreased failure free survival compared to those without viable tumor [27].…”
Section: Role Of Surgery In Treatmentmentioning
confidence: 99%
“…Second look surgeries of residual tumor either during or at the end of therapy have previously been evaluated. Persistence of radiographic masses at the end of therapy is well known, but biologic potential is uncertain, and resection of residual masses at the end of therapy has not been associated with improved outcome [26]. However, second look surgeries may demonstrate whether viable tumor is present, which has decreased failure free survival compared to those without viable tumor [27].…”
Section: Role Of Surgery In Treatmentmentioning
confidence: 99%
“…Standard cross-sectional imaging (CT or MRI) performed either early (23) or late in the treatment plan (24) fail to predict disease recurrence. A single institutional review demonstrated that patients who had a negative PET following induction chemotherapy and radiotherapy had a superior local-relapse free survival than patients with a positive PET (94% vs. 75%, 0=0.02) (25) In the future, FDG-PET might replace conventional staging imaging studies, particularly for lymph node disease.…”
Section: Introductionmentioning
confidence: 99%
“…This approach was beneficial for confirming the pathologic tumor response, for identifying patients who required second-line chemotherapy. However, the impact of a second-look procedure on survival in group III patients was unclear [21] [30]. In general, modern risk-based multimodality therapeutic protocols including chemotherapy for primary cytoreduction and eradication of both macroscopic and microscopic disease, surgery if feasible, and radiation therapy to control microscopic local residual disease, leads to improved outcomes in children with RMS [23].…”
Section: Discussionmentioning
confidence: 99%